Cytochrome P450 diversification and hostplant utilization patterns in specialist and generalist moths: Birth, death and adaptation. Issue 21 (7th October 2017) - Calla, Bernarda; Noble, Katherine; Johnson, Reed M.; Walden, Kimberly K. O.; Schuler, Mary A.; Robertson, Hugh M.; Berenbaum, May R.
Abstract: Across insect genomes, the size of the cytochrome P450 monooxygenase (CYP) gene superfamily varies widely. CYPome size variation has been attributed to reciprocal adaptive radiations in insect detoxification genes in response to plant biosynthetic gene radiations driven by co‐evolution between herbivores and their chemically defended hostplants. Alternatively, variation in CYPome size may be due to random "birth‐and‐death" processes, whereby exponential increase via gene duplications is limited by random decay via gene death or transition via divergence. We examined CYPome diversification in the genomes of seven Lepidoptera species varying in host breadth from monophagous ( Bombyx mori ) to highly polyphagous ( Amyelois transitella ). CYPome size largely reflects the size of Clan 3, the clan associated with xenobiotic detoxification, and to some extent phylogenetic age. Consistently across genomes, families CYP6, CYP9 and CYP321 are most diverse and CYP6AB, CYP6AE, CYP6B, CYP9A and CYP9G are most diverse among subfamilies. Higher gene number in subfamilies is due to duplications occurring primarily after speciation and specialization ("P450 blooms"), and the genes are arranged in clusters, indicative of active duplicating loci. In the parsnip webworm, Depressaria pastinacella, gene expression levels in large subfamilies are high relative to smaller subfamilies. Functional and phylogenetic data suggest a correlation between highly dynamic loci (reflective of extensive gene duplication, functionalization and in some cases loss) and the ability of enzymes encoded by these genes to metabolize hostplant defences, consistent with an adaptive, nonrandom process driven by ecological interactions.